PEMETAAN KONSENTRASI (SUB JURUSAN) DARI PERSPEKTIF PERILAKU MENTAL ACCOUNTING MAHASISWA BARU PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU 2015 (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The purpose of this research is to map the selection of sub majorâs freshmen Economic Education FKIP Riau University. The determination of this department only after entering into three semesters, students will be divided into accounting concentration and cooperatives, before this division, the research needs to be done to predict the concentration to where they will be placed later, and to find out how the behavior of the students mental accounting. This research is an exploratory study through a survey with descriptive methods (descriptive research). The data used is primary data obtained from semi-structured interview to Economic Education Students. This study took 93 samples of the new students of Economic Education. Based on the results of research and discussion, it was concluded that; 1) most of the students have determined the choice before they are grouped by program of study based on the introduction of accounting; it is based on the consideration that the field of study that they would choose to have a bright career prospects for their future. 2) student financial planning by classifying according to his needs. Financial management of the new students in the economics of education they also apply as they get in the lecture material, which money should actually managed to classify them according to their needs. 3) the formation of behavioral mental accounting in freshman economics education, were more influenced by the character formed from backgrounds of students before they studied accounting in college, during high school they had known accounting and by the many alumni who after finishing in economic education, they can devote their knowledge in various institutions and private companies (non-teachers).Based on these findings, it is recommended to economic education courses to determine the selection of majors in addition to the introductory value based accounting, must also consider the interests and choices of the student as well as the background of his high school education.Keywords: Mapping, mental attitude accounting